Revisiting unity and diversity in federal countries : changing concepts, reform proposals and new institutional realities - Gagnon, Alain; Burgess, Michael (Studies in territorial and cultural diversity governance, 2018)
The principal aim of this book is to revisit the basic theme of "unity and diversity" that remains at the heart of research into federalism and federation. It is time to take another look at its contemporary relevance to ascertain how far the bifocal relationship between unity and diversity has evolved over the years and has been translated into changing conceptual lenses, practical reform proposals and in some cases new institutional practices.